Construction Of The Production Of Granule Bat Fertilizer In Smk Muhammadiyah 5 Panceng Gresik - Mohammad Dian Kurniawan; Deny Andesta; Nina Aini Mahbubah (INNOVATION RESEARCH JOURNAL, 2020)
Fertilization is an action in plant care. Fertilization provides additional nutrients for the soil. Fertilization has a large influence on plant growth and production. Fertilization consists of organic and inorganic fertilizers. Both of these fertilizers must be balanced so that the nutrient content can be maintained properly. The use of fertilizers an organic fertilizer that is widely used, but the use of chemical fertilizers on an ongoing basis will reduce the level of soil fertility. This must be balanced with organic fertilizer. One of the organic fertilizer is guano fertilizer. This fertilizer is fertilizer made from animal waste, namely bats. This fertilizer has a very good content including nitrogen, phosphorus, and potassium. Knowledgethis fertilizer will still be low, so that an introduction and practice about guano fertilizer is needed. Therefore a community service activity was carried out on the development of the manufacture of guano fertilizer. Guano fertilizer development is carried out in the form of granules (granules). The targets of this service are vocational students who are related to agriculture. Vocational students are selected as the young generation to know about organic fertilizers and are able to contribute to the implementation of the agricultural industry. Community service activities were carried out with a presentation of the theory and practice of making guano fertilizer. As a result of this activity, students learned about organic fertilizer, namely guano fertilizer and its contents, nutrient content in the soil, balance in maintaining nutrient content in the soil, the practice of making guano fertilizer, and the creation of granule form from guano fertilizer.